Barn Owl Productivity Response to Variability of Vole Populations - Pavluvčík, Petr; Poprach, Karel; Machar, Ivo; Losík, Jan; Gouveia, Ana; Tkadlec, Emil (PloS one, 2015)
We studied the response of the barn owl annual productivity to the common vole population numbers and variability to test the effects of environmental stochasticity on their life histories. Current theory predicts that temporal environmental variability can affect long-term nonlinear responses (e.g., production of young) both positively and negatively, depending on the shape of the relationship between the response and environmental variables. At the level of the Czech Republic, we examined the shape of the relationship between the annual sum of fledglings (annual productivity) and vole numbers in both non-detrended and detrended data. At the districts' level, we explored whether the degree of synchrony (measured by the correlation coefficient) and the strength of the productivity response increase (measured by the regression coefficient) in areas with higher vole population variability measured by the s-index. We found that the owls' annual productivity increased linearly with vole numbers in the Czech Republic. Furthermore, based on district data, we also found that synchrony between dynamics in owls' reproductive output and vole numbers increased with vole population variability. However, the strength of the response was not affected by the vole population variability. Additionally, we have shown that detrending remarkably increases the Taylor's exponent b relating variance to mean in vole time series, thereby reversing the relationship between the coefficient of variation and the mean. This shift was not responsible for the increased synchrony with vole population variability. Instead, we suggest that higher synchrony could result from high food specialization of owls on the common vole in areas with highly fluctuating vole populations.
Keywords: Reproduction; rozmnožování; druhová specificita; Population Dynamics; Strigiformes; Ecosystem; populační růst; Population Growth; Female; Models, Biological; zvířata; stochastické procesy; populační dynamika; roční období; ženské pohlaví; Male; Arvicolinae; Seasons; Czech Republic; biologické modely; Species Specificity; Animals; Stochastic Processes; Česká republika; mužské pohlaví; ekosystém; Stringiformes